2009
DOI: 10.3748/wjg.15.1816
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of acetylshikonin on human gastric carcinoma cell line SGC-7901 in vitro and in vivo

Abstract: AIM:To investigate the inhibitory effect of acetylshikonin on human gastric carcinoma cell line SGC-7901 and its mechanism. METHODS:MTT assay was used to assess the inhibitory effect of acetylshikonin on proliferation o f S G C-7 9 0 1 c e l l s . A p o p t o s i s -i n d u c i n g e f f e c t was determined by flow cytometry and terminal deoxynucleotidyl transferase-mediated dUTP-biotin nick end-labeling with Hoechst staining. Expression of mRNA and protein in Bcl-2 and Bax was analyzed by reverse transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 19 publications
4
24
0
1
Order By: Relevance
“…It has been reported earlier that shikonin possesses tumour cell-killing activity against a variety of cell lines (Min et al 2008;Wu et al 2004;Zeng et al 2009). Also ACS demonstrated antitumour effects in malignant cell lines (Xiong et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported earlier that shikonin possesses tumour cell-killing activity against a variety of cell lines (Min et al 2008;Wu et al 2004;Zeng et al 2009). Also ACS demonstrated antitumour effects in malignant cell lines (Xiong et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In recent studies, shikonin and its derivatives were demonstrated to induce apoptosis of tumor cells. It has been reported that shikonin could induce A375-S2 cells apoptosis and cell cycle arrest through caspase-9 dependent pathways (Wu et al, 2004a); acetylshikonin induced SGC-7901 cells apoptosis by downregulating Bcl-2 expression and upregulating Bax expression (Zeng et al, 2009); shikonin induced apoptosis in HeLa cells via caspase-3 activation, blockage of DNA synthesis, and cell cycle arrest (Wu et al, 2004b); shikonin could induce apoptosis in COLO 205 cells via modulating the Bcl-2 family, upregulating p27, p53, releasing cytochrome c, and sequentially activating caspases (Hsu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Aikete injection is composed of acetylshikonin and β,β-dimethylacrylshikonin (Figure 1), the two main effective anti-tumor components of shikonin (Hu et al, 2006;Kundakovic et al, 2006;Zeng et al, 2009). Although the anti-tumor effect of acetylshikonin and β,β-dimethylacrylshikonin has been reported widely, little is known about the effects of the combination of the two components on cancer cells.…”
Section: Research Articlementioning
confidence: 99%
“…Hsu PC et al demonstrated that shikonin induced apoptosis through up-regualtion of p27, p53, Bax and activation of caspases in human colorectal carcinoma cells (Hsu et al, 2004). Zeng Y et al also found that acetylshikonin led to cell apoptosis in human gastric carcinoma cell line SGC-7901 via elevation of Bax /Bcl-2 ratio (Zeng et al, 2009). Recently, we reported that β,β-dimethylacrylshikonin induced mitochondria-dependent apoptosis via ERK1/2 pathway in human gastric cancer SGC-7901 cells (Shen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%